Hubungan Pola Asuh Orang Tua Dan Interaksi Sosial Siswa Terhadap Motivasi Belajar Siswa Di SMA Negeri 1 Tilamuta Kabupaten Boalemo - Yusni Abas; Roy Hasiru; Agil Bahsoan; Sudirman Sudirman; Risca Marsanti Halid; Ardiansyah Ardiansyah (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the relationship between parenting patterns and students' social interactions in students' learning motivation at Smal Negeri 1 Tilalmutal Kalbupalten Boallemo. The research approach used in this study is a qualitative approach using a descriptive research method. The data used are primary data obtained from distributing questionnaires to students of XI IPS D at Smal Negeri 1 Tilalmutal Kalbupalten Boallemo. The number of samples in this study was 58 respondents with a random sampling technique. The data collection techniques in this study were: Observation, Questionnaires and Documentation.The results of this study indicate that the X1 variable of Parenting Patterns and the X2 variable of Social Interaction have an effect on Student Learning Motivation at SMAL Negeri 1 Tilalmutal by 43.6%. While the rest is influenced by traffic variables that were not studied in this study.